TOXIC IMPACT OF PHBNTHOATE ON SOME FUNCTIONAL ASPECTS OF NITROGEN METABOLISM IN TISSUES OF THE FISH CHANNA PUNCTATUS - Rao, K Sivaprasada; Rao, K R S Sambasiva; Babu, K Sreenivasa; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
The tissue total proteins decreased with a raise in the free amino acid levelin the fishes exposed to sublethal concentrations of phenthoate. However, ammoniaand urea contents and the activity levels of glutamate dehydrogenase showedvariable trend among the tissues during phenthoate intoxication. The results arediscusssed in relation to the adaiptability of the fish by recycling the toxic ammoniato the less toxic urea and towards the synthetic processes under phenthoate toxicimpact.